The relationship between capital structure and financial performance of South Africa’s schedule 2 state owned entities - Marotholi, Tsholofelo (My University, 2018)
In South Africa, State-Owned Entities (SOEs) are used as instruments to advance government’s developmental objectives, which are aimed at eliminating unemployment, poverty and inequality. In doing so, these public entities are expected to remain financial sustainable over the long-term, without posing a risk to the national resources. To address this dual mandate, public entities require an optimal capital structure mix (equity and debt) to fund long-term assets that will generate sufficient funds to allow the public entities to remain financially sustainable over the long term. Various empirical studies have indicated that there is some kind of association between capital structure and financial performance. This study attempts to explore the relationship that exists between capital structure and the financial performance of Schedule 2 SOEs. Understanding the effect that the capital structure has on the performance of SOEs could assist public entities and/or the government to arrive at the appropriate level of capital structure that would enable these SOEs to pursue their respective mandates effectively. To explore this relationship, a sample of 18 SOEs from a population of 21 Schedule 2 public entities, was used. The data from the study was extracted from the audited annual reports of the respective entities, covering the period from 2005 to 2015. The dynamic General Method of Moments (GMM) model was applied to the data employed in this research. The results of the study produced mixed results. Capital structure measures long-term debt to total assets is positively and significantly related to return on assets (ROA), but negatively and significantly associated to return on equity (ROE), net profit margin (NPM) and operating margin (OM). With respect to short-term debt to total assets (STDA), there is a significantly negative relationship between ROA and OM. However, STDA is positively and significantly related to ROE and NPM. Furthermore, the study results are in line with the trade-off theory and traditional theory on capital structure, which advocate that there are benefits to the usage of debt. However, excessive application of debt could erode the benefits associated with its usage. Therefore, the management of SOEs will need to continuously rebalance the combination of equity and debt within the entities as they undertake different projects that will satisfy government’s developmental objectives, thus ensuring that the firms’ capital structure is at its optimal level.
Wits Business School University of Witwatersrand Master of Management in Finance and Investment Johannesburg, South Africa, 2018
Keywords: Corporations--Finance; Capital--South Africa